Tathbiq aṭ-Tariqah at-Tamṣiliyah Biistikhdam Kitáb 100 Muḥadaṣah ‘Arabiyah al-Mujallad al-Awwal Litanmiyati Máharah al-Kalám Lada at-Thalabah Fi al-Marhalah al-Muhammadiyah 06 Dau Malang - Harahap, Arpin Aminuddin Hrp; Mamluatul Hasanah; Faisol (Tarling : Journal of Language Education, 2025)
The objectives of learning Arabic will be achieved well if teachers pay attention to the methods used during learning, and inappropriate methods will affect the quality of learning. Among the fun and interesting methods that can achieve the goal of learning Arabic, especially good speaking skills, is role play. The purpose of this study was to determine how to implement the role play method with the book 100 Muhadasah Arabiah volume one at SMP Muhammadiyah 06 Dau Malang, as well as to determine the advantages and disadvantages. The approach used in this research is descriptive qualitative with a case study research type. Techniques of collecting data use interviews, observations, and documents. The data analysis techniques are data collection, data reduction, data presentation, and conclusions. The research results show that the implementation of the role play method with the book 100 Arabian muhadasah consists of three stages, namely: (1) he preparation stage includes conveying learning objectives and using methods. (2) The implementation stage consists of dividing into groups, discussing scenarios, dividing roles and role playing. (3) The closing stage consists of performance evaluation and conclusions. Among the advantages of this method when applied is the increase in students' enthusiasm and their confidence in speaking, while the disadvantages are that it takes a long time and there are limited resources or tools in its implementation.